Relationship between soil characteristics and altitude with the sensory quality of coffee grown under agroforestry systems in Cusco, Peru - Márquez, Fanny Rosario (2020)
Peru produces coffees of different qualities because it has very diverse ecosystems, the production of specialty coffees is an opportunity for economic and social improvement for small producers considering that the price of coffee is related to the sensory quality of the drink in ever larger market niches. In this study, the effect of the physical-chemical characteristics of the soil and the altitude of the farms on the sensory quality of coffee was evaluated in 56 high-altitude coffee farms in agroforestry systems of the upper jungle of Cusco, the physical and chemical characterization was carried out of the soils of farms located between 1312 and 1910 meters above sea level in the Tunquimayo - Quellouno - Cusco area and the sensory quality of the coffee was evaluated using SCAA methodology. It was found that the acidity and the aluminum concentration of the soils increases with altitude, the levels of available phosphorus, calcium and exchangeable potassium are low, while the changeable magnesium is high. In the coffee sensory quality test, 50% of the farms obtained scores of 80 - 84, the same ones that qualify as Very Good specialty coffee; the altitude contributed positively to the increase in attributes such as personal appreciation, sweetness, balance, aroma and flavor; concluding that the altitude and soil characteristics such as phosphorus (P) and cation exchange capacity (CEC) influence the sensory quality of coffee.